Clinical, biomarker and endoscopic outcomes in patients with Crohn's disease treated with Ustekinumab: Multi‐centre real world study. Issue 3 (3rd May 2021) - Kamperidis, Nikolaos; Fenech, Valerie; Thoua, Nora; Cole, Alexander; Segal, Jonathan P.; Peake, Simon; Arebi, Naila
Summary: Background: Ustekinumab is a recognised treatment for moderate‐to‐severe Crohn's disease. We aimed to examine its effectiveness in an adult population in three London centres, and to identify patient, disease or drug‐related factors associated with effectiveness. Methods: A retrospective observational study on adults with Crohn's disease prescribed Ustekinumab between 2017 and 2019. The primary outcome was clinical response at Week 12. Other outcomes included clinical response at Week 52, clinical remission at Weeks 12 and 52, disease activity on biochemical markers (CRP and faecal calprotectin), endoscopic remission (resolution of ulceration at ileocolonoscopy) and fistula improvement or closure in a subset of patients with perianal fistulising disease. Results: A total of 134 patients with a median follow‐up of 12 months. Clinical response and remission rates were 58% and 46% at 12 weeks and 64% and 57.5% at 52 weeks respectively. Median HBI score reduced from 9 to 5 at 12 weeks and to 4 at 52 weeks. Concomitant reduction in C‐reactive protein and calprotectin and endoscopic healing or improvement (52%). Twelve per cent experienced at least one adverse event, 22% discontinued Ustekinumab and 31% required rescue therapy. Rescue therapy with corticosteroids was independently associated with short time to treatment discontinuation. Conclusion: Clinical response and remission rates were comparable to other studies. Previous exposure to biologics and longer disease duration were associated with less favourable outcomes. Rescue therapy with corticosteroids was the only factor independently associated with treatment discontinuation. Future studies should examine outcomes of Ustekinumab prescribed early in the disease course.